(untitled) (International Conference on Computers in Education, 2020)
This study explores students’ interest profile and the extent of their interest towards educational technology over a 14-week period. A survey was used to explore students’ interest profile while artifacts from an e-portfolio were used to understand the extent of their interest. The results revealed that students felt good about educational technology and were drawn to it. The findings proved encouraging given that it is crucial to nurture future habitual interest-driven creator teachers who are always excited to discover more about educational technology to enhance their teaching in classrooms.